The Italian secretary : a further adventure of Sherlock Holmes - Carr, Caleb, 1955- (St. Martin's Griffin, 2009)
FOUL WHISPERINGS<U+2026> Mycroft Holmes's encoded message to his brother, Sherlock, is unsubtle enough even for Dr. Watson to decipher: a matter concerning the safety of Queen Victoria herself calls them to Edinburgh's Holyroodhouse to investigate the confounding and gruesome deaths of two young men<U+2015>horrific incidents that took place with Her Highness in residence. The victims were crushed in a manner surpassing human power. And while recent attempts on Her Majesty's life raise a number of possibilities, these intrigues also seem strangely connected to an act of evil that took place centuries earlier<U+2026> <U+2026>UNNATURAL DEEDS For indeed, the slaying of David Rizzio, music master and friend to Mary, Queen of Scots, was an extraordinarily brutal and treacherous act<U+2015>even for a time when brutality and treachery were the order of the day. Now, the ghosts of Holyroodhouse are being reawakened by someone with a diabolical agenda of greed, madness, and terror as Holmes and Watson set out to trap a killer who is eager to rewrite history in blood...